Effect of Molasses and Fermented Juice of Epiphytic Lactic Acid Bacteria on the Fermentation Characteristics and Nutrient Compositions of Cassava Leaves Silage - Achara Lukkananukool; Chanathip Thammakarn; Kanokrat Srikijkasemwat; Min Aung; Yin Yin Kyawt (My University, 2018)
T he use of crop residues and agricultural by-products in animal feeding is a very common practice to ensure the feed supply for livestock production.Forage crops can be conserved through the fermentation process of ensiling, in which lactic acid bacteria (LAB) ferment water soluble carbohydrates (WSC) into organic acids (mainly lactic acid) in an anaerobic environment.As a result, pH is decreased and forage is conserved (Weinberg et al., 2001).Among the tropical crops, cassava is the most nutritional potential and it had been used as feed for livestock because of its remarkable carbohydrate and protein contents.Cassava leaves are the by-product of tuber production and rich in proteins (14-40%), vitamins, minerals, and carotenoids (Adewusi and Bradbury, 1993).However, it is difficult to ensile the high protein legumes and tropical forage crop because of their low concentration of WSC and high buffering capacity (Mc.Donald et al., 1991; Titterton and Bareeba, 2000), and resulted in lower fermentation quality, intake, and digestibility (Niimi and Kawamura, 1998).Thus, the additives such as fermentation stimulants, fermentation inhibitors, aerobic deterioration
Keywords: Silage; Food composition and properties